PENERAPAN MODEL PEMBELAJARAN RADEC BERBANTUAN MEDIA GAMES BERBENTUK APLIKASI WORDWALL TERHADAP HASIL BELAJAR PESERTA DIDIK - Aini, Aini Meutiah N; Muh. Erwinto Imran; Ana Dhiqfaini Sultan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the application of the Radec learning model assisted by media games in the form of a wordwall application on the learning outcomes of students in the subject of social studies in grade V at the SPF Unit of Elementary School Inpres Bertingkat Kaluku Bodoa. The background of this study is based on the low learning outcomes of students due to the lack of use of learning media and not varied. This study used a pre-experimental method with a one-group pretest-posttest design. The research sample consisted of 28 students who applied the SPF Unit of Elementary School Inpres Bertingkat Kaluku Bodoa. Data were collected through pretests and posttests, and analyzed using the n-Gain test using SPSS. The results showed a significant improvement in student learning outcomes. The average posttest score increased from 55.96 to 85.03. The n-Gain test showed a Gain value of g > 0.70 for 10 students and 0.30 ≤ g < 0.70 for 18 students, indicating that the implementation of the Radec learning model, supported by games in the form of a wordwall application, significantly improved student learning outcomes. The conclusion of this study confirms that the implementation of the Radec learning model, supported by games in the form of a wordwall application, can improve student learning outcomes in science. The implication of this research is the need for innovative, technology-based learning media to enhance the effectiveness of learning in elementary schools.